A multi-wavelength study of the western lobe of W50 powered by the galactic microquasar SS 433 - Moldowan, A. (2005)
W50 remains the only supernova remnant (SNR) confirmed to harbor a microquasar: the powerful enigmatic source SS 433. Our past study of this fascinating SNR revealed two X-ray lobes distorting the radio shell as well as non-thermal X-rays at the site of interaction between the SS 433 eastern jet and the eastern lobe of W50. In this paper we present the results of a 75 ks Chandra ACIS-I observation of the peak of W50-west targeted to: (1) determine the nature of the X-ray emission and (2) correlate the X-ray emission with that in the radio and infrared domains. We have confirmed that at the site of interaction between the western jet of SS 433 and dense interstellar gas the X-ray emission is non-thermal in nature. The helical pattern observed in radio is also seen with Chandra. No correlation was found between the infrared and X-ray emission.